1984
DOI: 10.1227/00006123-198404000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Vasopressin in Brain Edema Formation: Further Evidence Obtained from the Brattleboro Diabetes Insipidus Rat with Experimental Subarachnoid Hemorrhage

Abstract: Brain water accumulation (1.2%) with an accompanying increase in the sodium content was observed in Wistar rats as early as 1 hour after experimental subarachnoid hemorrhage (SAH). After 6 and 24 hours, the water content was 1.3 and 1.4%, respectively, higher than that of control animals. In contrast, in Brattleboro diabetes insipidus rats the content of brain water and electrolytes had not changed significantly 1 hour after the administration of blood into the subarachnoid space. Increased brain water and sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 93%
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 93%
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…10 The hormone arginine vasopressin (AVP) was identified as a potential mediator of astrocytic cell swelling and subsequent fulminating edematous changes following cerebral injury. [11][12][13][14][15][16][17] It is thought that centrally-released AVP orchestrates the development of brain edema by inducing water and ionic movement. 18,19 Increased AVP levels activate the V1a receptor (V1aR), facilitate water transport across astrocytic cell membranes, and are associated with brain edema formation.…”
Section: Introductionmentioning
confidence: 99%